Oportunidades de mejora para los procesos de recepción, fabricación y despacho de máquinas despulpadoras de café - Pérez-González, Jairo Roberto; Cárdenas Cortés, Xiomy Carolina; Ocampo-Arias, Daniela; Ceballos, Yony Fernando (Ingeniería, 2022)
Context: Coffee is a popular drink obtained from the seed of a shrub called cafeto, which is ground and toasted in order to obtain the powder used for the elaboration of the drink. For its transformation, it is necessary to use different types of machines, which is an important market niche in the country’s economy. Therefore, it is necessary to identify opportunities for improvement in the activities of the process involving ordering, production, and dispatch of coffee pulping machines in a Colombian company. Method: By using simulation as a tool, a model is built which appropriately represents the reality of the company, starting with the delimitation of the problem, continuing the identification of key variables, the taking of samples and their statistical analysis, the construction of the simulation with its respective validation and verification processes, and ending with the analysis of results and possibilities of application in the company, together with the conclusions of the process. Results: Based on the scenarios elaborated, it is recommended to design a dispatch area to access information quickly and in a timely manner, together with the development of specialized software that allows digitizing orders and referrals, as well as with the planning of delivery routes for prioritized orders according to the key variables of the process. With the implementation of the suggestions above, the queue of assembled and non-dispatched machines was reduced by 51%, and the dispatches of coffee pulping machines increased by 49%, thus improving customer satisfaction. Conclusions: The investment required to implement the solution scenario represents medium-term returns, which, together with customer satisfaction, allows the company to be made competitive. A study of the logistics of dispatching orders is proposed, since this part of the problem is evident, but cannot be solved by simulation.